THE IMPACT OF CAPITAL EXPENDITURE, INVESTMENT, AND LABOR FORCE ON ECONOMIC GROWTH IN SOUTH KALIMANTAN - Muzdalifah Muzdalifah; Syahrituah Siregar (UPT Penerbitan Universitas Jember)
This study aims to analyze the influence of capital expenditure, investment, and labor force on the economic growth of regencies / cities in South Kalimantan. Approach in this research use explanatory research method. The analysis technique used is panel data regression with Fixed Effect Model (FEM). The results show that only the variable of the labor force significantly affects economic growth with a meaningful negative relationship that if an increase in economic growth will cause the total labor force to decline. The highest Individual Intercept is in Banjarmasin City, Banjar District, Hulu Sungai Tengah, whereas. Intercept Individual is lowest in Barito Kuala, Tapin and Hulu Sungai Selatan regencies, meaning that if the variable of Capital Expenditure, Private Investment and Labor is considered Constant, the highest Economic Growth occurs in Banjarmasin City followed by Banjar and Hulu Sungai Tengah Regency, while Growth Lowest economy in Barito Kuala District, Tapin and Hulu Sungai Selatan